Women's attitudes towards the medicalization of childbirth and their associations with planned and actual modes of birth. Issue 5 (October 2017) - Benyamini, Yael; Molcho, Maya Lila; Dan, Uzi; Gozlan, Miri; Preis, Heidi
Abstract: Problem: Rates of medical interventions in childbirth have greatly increased in the Western world. Background: Women's attitudes affect their birth choices. Aim: To assess women's attitudes towards the medicalization of childbirth and their associations with women's background as well as their fear of birth and planned and unplanned modes of birth. Methods: This longitudinal observational study included 836 parous woman recruited at women's health centres and natural birth communities in Israel. All women filled in questionnaires about attitudes towards the medicalization of childbirth, fear of birth, and planned birth choices. Women at <28 weeks gestation when filling in the questionnaire were asked to fill in a second one at ∼34 weeks. Phone follow-up was conducted ∼6 weeks postpartum to assess actual mode of birth. Findings: Attitudes towards medicalization were more positive among younger and less educated women, those who emigrated from the former Soviet Union, and those with a more complicated obstetric background. Baseline attitudes did not differ by parity yet became less positive throughout pregnancy only for primiparae. More positive attitudes were related to greater fear of birth. The attitudes were significantly associated with planned birth choices and predicted emergency caesareans and instrumental births. Discussion: Women form attitudes towards the medicalization of childbirth which may still be open to change during the first pregnancy. More favourable attitudes are related to more medical modes of birth, planned and unplanned. Conclusion: Understanding women's views of childbirth medicalization may be key to understanding their choices and how they affect labour and birth.